Analisis Pengaruh Earning Per Share (EPS), Price to Book Value (PBV) dan Price Earning Ratio (PER) Terhadap Return Saham Pada Industri Makanan dan Minuman di Bursa Efek Indonesia 2010-2013. - Kartika Ningsih, Siti; , Ir. Maulidiyah Indira Hasmarini, MS; , Drs. Harun M.H (2016)
This study aims to determine the effect of variable Earning Per Share, Price to Book Value and Price Earning Ratio of Equity Return on food and beverage industry in Indonesia Stock Exchange in 2010-2013. The effect of variable Earning Per Share, Price to Book Value and Price Earning Ratio of Stock Return food and beverage companies will be analyzed using multiple linear analisis regresi. The purpose of this study was to determine the positive effects EOS, PBV and PER on Stock Return the food and beverage industry either simultaneously or partial. The data used are secondary data, Return Shares of food and drinks, Earning Per Share, Price to Book Value, Price Earning Ratio. Data obtained from the Indonesian Capital Market Directory (ICMD). The method used is multiple linear regression analysis, the classic assumption test, and hypothesis testing. From the calculation (EPS, PBV, PER) has the ability to influence the Stock Return of 0969, or 96.6%, while the rest influenced by other variables not included in this study. And after the test using test F known that EPS, PBV simultaneously affect the stock return, while the PER does not affect the stock return. And the t-test is known that EPS, PBV and PER partially have an influence on Stock Return.